1967
DOI: 10.1099/00221287-48-3-391
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Organic Cations on the Gram-negative Cell Wall and Their Bactericidal Activity with Ethylenediaminetetra-acetate and Surface Active Agents

Abstract: S U M M A R YWhen Gram-negative cell walls were damaged by lysozyme and ethylenediaminetetra-acetic acid (EDTA) in tris buffer, tris played an active role through its action as an organic cation. Other organic cations such as aliphatic amines and quaternary ammonium compounds were more effective than tris in modifying the cell wall and making it permeable to other solutes. The most effective organic cations had one C,, to CI6 alkyl chain. At ~H I o , EDTA roo pg./ml and N,N-dimethyldodecylamine (DDA) 2.5 ,ug./… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
27
0

Year Published

1968
1968
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(33 citation statements)
references
References 7 publications
(2 reference statements)
5
27
0
Order By: Relevance
“…These earlier studies used Tris-buffered medium during growth, which may condition cells. However, adverse effects of Tris have been reported (13,34). In addition, it was found that (i) Tris-Cl and Tris-acetate were nearly equivalent in toxicity, (ii) addition of KGiu protected permeabilized cells against the adverse effects of Tris, and (iii) viability of unpermeabilized cells was not affected by Tris at the concentrations used here (data not shown).…”
Section: Methodsmentioning
confidence: 71%
“…These earlier studies used Tris-buffered medium during growth, which may condition cells. However, adverse effects of Tris have been reported (13,34). In addition, it was found that (i) Tris-Cl and Tris-acetate were nearly equivalent in toxicity, (ii) addition of KGiu protected permeabilized cells against the adverse effects of Tris, and (iii) viability of unpermeabilized cells was not affected by Tris at the concentrations used here (data not shown).…”
Section: Methodsmentioning
confidence: 71%
“…This work was prompted by reports that EDT A could enhance the action of antiseptics (Brown & Richards, 1965;Caplin & Chapman, 1976;Goldschmidt et at., 1972) and that Tris increased the activity of EDTA (Voss, 1967;Goldschmidt and Wyss, 1967). It was hoped that the addition of these agents would enable the concentration of chlorhexidine to be reduced so that it was less erosive and also overcome any resistance that has been previously reported by Stickler (1974).…”
Section: Introductionmentioning
confidence: 99%
“…Although EDTA has been found to extract lipopolysaccharide from Escherichia coli, the bacteria remained viable under the conditions used (Leive, 1965). Except when used in conjunction with organic cations (Wolin, 1966;Goldschmidt & Wyss, 1967;Voss, 1967), EDTA does not seem to be highly toxic for Gram-negative bacteria other than pseudomonads (Gray & Wilkinson, 1965 a;Wilkinson, 1967). This hypersensitivity to EDTA might prove to be a useful characteristic in the taxonomy of the pseudomonads (Shively & Hartsell, 1964;Wilkinson, 1967 (1956) without prior hydrolysis of samples, and was expressed as glucose.…”
Section: Introductionmentioning
confidence: 99%